Irrigation Water Quality Index Assessment of Ele River in Parts of Anambra State of Nigeria - , C. Emmanuel Chukwuma, C. Godwin Chukwuma, I. Joseph Uba, C. Louis Orakwe, N. Kingsley Ogbu (Archives of Current Research International, 2016)
Due to concentration of industries in the study area and indiscriminate disposal of industrial effluent into Ele River, this study therefore aims at assessing the suitability of Ele River in Nnewi, Anambra State of Nigeria for irrigation purpose. Water samples were collected from three sampling points: Point 1 is at the point of effluent entrance, while point 2 is 100 m away from the point of discharging effluent and point 3 is 250 m away from the discharging effluent. To determine the suitability of Ele River as dry season (for the months of November, December and January) irrigation water supply, irrigation water quality index was used. Variables used for the assessment includes: Electrical Conductivity (EC), Sodium Absorption Ratio (SAR), Cl-, Total Hardness, Na+ and HCO3. These variables were integrated to obtain a single number that represents the irrigation water quality. The result of the study shows that the IWQI of the month of November ranges from 39.88 at point 1 to 40.07 and 43.03 at point 2 and 3 respectively. While the month of December had 41.02, 42.51 and 43.33 at point 1, 2 and 3 respectively. The IWQI obtained for the month of January were 34.25, 36.96, and 40.25 for point 1, 2 and 3. This indicates that the River is severely polluted and the water quality could be classified as between high restriction to severe restriction usage based on water use restriction criteria in this study.